2022
DOI: 10.1002/mp.15668
|View full text |Cite
|
Sign up to set email alerts
|

Development of an ultra‐thin parallel plate ionization chamber for dosimetry in FLASH radiotherapy

Abstract: Background: Conventional air ionization chambers (ICs) exhibit ion recombination correction factors that deviate substantially from unity when irradiated with dose per pulse magnitudes higher than those used in conventional radiotherapy. This fact makes these devices unsuitable for the dosimetric characterization of beams in ultra-high dose per pulse as used for FLASH radiotherapy. Purpose: We present the design, development, and characterization of an ultrathin parallel plate IC that can be used in ultra-high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…Reducing the electrode distance has been shown to be more effective than increasing the chamber voltage. Based on theoretical considerations and experiments, it has been shown that a reduction of the electrode distance down to 0.25 mm can be well suited [19] . In this work, well-guarded vented parallel-plate ionization chambers (PPIC) with three different electrode distances are investigated experimentally and by means of simulations under ultra-high DPP conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Reducing the electrode distance has been shown to be more effective than increasing the chamber voltage. Based on theoretical considerations and experiments, it has been shown that a reduction of the electrode distance down to 0.25 mm can be well suited [19] . In this work, well-guarded vented parallel-plate ionization chambers (PPIC) with three different electrode distances are investigated experimentally and by means of simulations under ultra-high DPP conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Until early 2021, "active" dosimeters were not available to measure such beams properly [6][7][8][9][10][11][12]. Then, two promising new devices were presented and tested: the ultra-thin ionization chamber, mainly studied and developed by F. Gomez Rodriguez et al [10][11][12][13][14], and the Flash diamond, developed by M. Marinelli and G. Verona Rinati et al [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…In this work a new theoretical approach to Ultra High Dose per Pulse (UHDP) and Ultra High Dose Rate (UHDR) measurements by means of a gas chamber is considered and discussed. In general, the analytical description of ion collection under such conditions is not feasible [13,14,17]. However, the general equation can be simplified by choosing some parameters properly so that an analytical description can be derived even in UHDP/UHDR conditions.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations